Hubungan Parasosial Army di Weverse (Studi Pada Komunitas Army Balikpapan) - Ulandari, Kristin Vidyas; Rohmah, Ainun Ni’matu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Parasocial relationships is the participation of fans who connect with an idol and become emotionally attached to them because the process satisfy each fan individually. The parasocial relationship that occurs between fans of the K-pop group BTS and their fans, namely ARMY, is established on the digital media Weverse. The aim of this research is to understand the description of parasocial relationships by looking at the levels of fan parasocial interaction: Entertainment Social Value, Intense Personal Feeling, Bonderline Pantalogical Tendency. This research employs the phenomenological method, a qualitative approach that allows for detailed observation and hearing of people's individual explanations and understandings based on their experiences. The sampling technique in this research used purposive sampling technique. Sampling took the form of observation, documentation and in-depth interviews as primary data analyzed using the Miles and Huberman model. According to the study's findings, fans' emotional attached to BTS were shown by ARMY's parasocial interactions, which included motivation aspect at the Entertainment Social Value level, intensity aspect at the Intense Personal Feeling level, and obsession aspect, willing to do anything behaviour, irrational and uncontrollble thinking at the Bonderline Pantalogical Tendency level.